Sustainable Innovations in Home Decor: Exploring Eco-friendly Paint Materials and Recycled Interior Applications - Chanchal Kumari; Deepti Pandey Rana (International Journal of Sustainability, 2024)
This paper delves into sustainable practices in home decorating, particularly focusing on eco-friendly paint products and innovative interior design solutions. It underscores the significance of zero-VOC and low-VOC coatings for indoor air quality and environmental safety, advocating for their use. Natural colors derived from plant extracts, clay, and minerals are highlighted for their biodegradability and availability in earthy tones, emphasizing their contribution to environmental sustainability. Milk-based paints are explored for their energy efficiency, while clay paints are noted for their moisture prevention properties. The circular economy benefits of recycled paint are also discussed. Water-based paints are recommended for their minimal environmental impact and easy cleaning, with plant-derived colors noted for their role in reducing the overall environmental footprint of decorating projects. Shifting focus to sustainable interior design, bamboo emerges as a rapidly renewable material suitable for flooring and furniture. Other materials such as recycled glass, coir,cork, reclaimed wood, recycled metal, mushroom mycelium, plastic recycling, hemp, and upcycled fabrics and paper composites are also highlighted for their eco-friendly attributes. The paper concludes by stressing the importance of considering materials throughout their lifecycle to promote a healthy home environment. It advocates for responsible consumption in color and interior design choices, emphasizing the need for sustainability in both product selection and design processes. Overall, the paper serves as a comprehensive guide for individuals looking to adopt sustainable practices in their home decorating endeavors.
Keywords: Cork Flooring; Paper Composites; Plastic Recycling; Reclaimed Wood; Recycled Metal; Upcycled Fabrics; Zero-VOC and Low-VOC Coatings